2019
DOI: 10.4236/jbm.2019.712005
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac-Induced Kidney Damage in Wistar Rats: Involvement of Antioxidant Mechanism

Abstract: Kidney damage has been associated with administration diclofenac, a phenylacetic acid derivative belonging to the nonsteroidal anti-inflammatory drugs (NSAIDs), which is commonly used for the treatment of various diseases such as rheumatoid arthritis, ankylosing spondylitis, acute muscle pain conditions and osteoarthritis. This study investigated the exact mechanism of diclofenac in renal toxicity by determining the involvement of oxidative stress in rats. Adult male Wistar rats were divided into two groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
(35 reference statements)
0
6
1
1
Order By: Relevance
“…5a). In contrast with another authors that found increased levels of malondialdehyde (MDA) and hydrogen peroxide (H 2 O 2 )/ROS in smaller doses [28], NTR treated diclofenac 100 mg/kg did not increase LOOH herein. However, as we do not directly quantify reactive oxygen species, we cannot infer the absence of oxidative damage in the NTR.…”
Section: Resultscontrasting
confidence: 74%
“…5a). In contrast with another authors that found increased levels of malondialdehyde (MDA) and hydrogen peroxide (H 2 O 2 )/ROS in smaller doses [28], NTR treated diclofenac 100 mg/kg did not increase LOOH herein. However, as we do not directly quantify reactive oxygen species, we cannot infer the absence of oxidative damage in the NTR.…”
Section: Resultscontrasting
confidence: 74%
“…This particular aspect highlights the fact that diclofenac may induce AKI via a different primary pathological mechanism. It is postulated that a mechanism related to the induction of oxidative stress and/or reduction of antioxidant capacity may be determinant for diclofenac-induced nephrotoxicity [ 14 , 15 ]. In this sense, investigations have shown that through oxidative stress, increased cytokine release, and nuclear factor κB (NFκB) activation, diclofenac may induce AKI [ 1 , 9 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study confirms previous findings that the administration of diclofenac sodium leads to an increase in serum levels of urea, uric acid, and creatinine. Urea is a byproduct of protein metabolism and its accumulation in the blood can be attributed to a decrease in glomerular filtration rate (GFR) caused by diclofenac sodium 36 . This drug inhibits the production of prostaglandins, which play a vital role in maintaining GFR.…”
Section: Discussionmentioning
confidence: 99%